2004
DOI: 10.1097/00019501-200402000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidants on coronary microvascular spasm induced by epicardial coronary artery endothelial injury in pigs

Abstract: Chronic administration of antioxidants suppressed microvascular hypercontraction, suggesting that it may be a promising therapeutic strategy for treating coronary microvessel disorders, including microvascular angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…It is well known that ROS downregulates NO production [24][25][26] and NO impairment has been shown to be involved in coronary vasospasm [27][28][29] . Our previous report first showed that repeated endothelial denudation induced the downregulation of eNOS expression in the coronary microvessels in this model 22) . Also, the downregulation of eNOS expression in downstream microvessels of denuded LAD was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It is well known that ROS downregulates NO production [24][25][26] and NO impairment has been shown to be involved in coronary vasospasm [27][28][29] . Our previous report first showed that repeated endothelial denudation induced the downregulation of eNOS expression in the coronary microvessels in this model 22) . Also, the downregulation of eNOS expression in downstream microvessels of denuded LAD was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Our previous study have shown that blockade of ROS generation by vitamin C and gluthatione attenu- ated coronary microvascular spasm in the same model, suggesting the involvement of ROS in coronary microvascular spasm induced by endothelial denudation 22) . A recent human study also suggested a role of ROS in the pathogenesis of epicardial coronary artery spasm 23) .…”
Section: Discussionmentioning
confidence: 78%
“…We developed porcine coronary artery spasm model induced by repeated epicardial coronary artery endothelial denudation, mimicking the endothelial injury, which may occur repeatedly in the progression of atherosclerosis during a long lifetime. In this model, epicardial coronary artery spasm and microvascular spasm are produced easily by the administration of serotonin and acetylcholine [7][8][9]. We reported that in this model epicardial coronary artery spasm and microvascular spasm are induced spontaneously in the conscious state without using any drugs [10].…”
Section: Introductionmentioning
confidence: 96%
“…There is a growing body of evidence which indicate that oxidative stress plays an important role in the initiation and progression of atherosclerosis and cardiovascular diseases (2)(3)(4)(5)(6)(7). Studies on human and animal models have documented that excessive free radicals production can result in decreased cell survival, altered membrane phospholipid asymmetry, hypercoagulability, and increased adhesion to endothelial cells (6,(8)(9)(10). Platelet involvement in the pathogenesis of thrombosis-related complications is well documented.…”
Section: Introductionmentioning
confidence: 99%